The Case for Industrial Policy : A Critical Survey - Pack, Howard; Saggi, Kamal (World Bank, Washington, DC, 2012)
What are the underlying rationales for industrial policy? Does empirical evidence support the use of industrial policy for correcting market failures that plague the process of industrialization? To address these questions, the authors provide a critical survey of the analytical literature on industrial policy. They also review some recent industry successes and argue that only a limited role was played by public interventions. Moreover, the recent ascendance of international industrial networks, which dominate the sectors in which less developed countries have in the past had considerable success, implies a further limitation on the potential role of industrial policies as traditionally understood. Overall, there appears to be little empirical support for an activist government policy even though market failures exist that can, in principle, justify the use of industrial policy.